2014
DOI: 10.1017/s0007114514003018
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency is associated with inflammatory cytokine concentrations in patients with diabetic foot infection

Abstract: Vitamin D has been recognised as a potent immunomodulator and its deficiency is common in different population groups including patients with diabetic foot infection. Diabetic foot infection reflects the altered immune status of the host. As cytokine regulation plays a significant role in infection and wound-healing processes, the present study aimed to evaluate the association between vitamin D status and inflammatory cytokine profiles in patients with diabetic foot infection. The serum concentrations of vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 32 publications
(27 reference statements)
6
73
1
2
Order By: Relevance
“…Our findings of a higher plasma IL-6 level in early pregnancy in women with vitamin D insufficiency is in accordance with previous reports demonstrating higher levels of plasma IL-6 in patients with diabetes and vitamin D insufficiency (32). In healthy women with preterm delivery (33) a higher level of IL-6 has been documented, indicating that proinflammatory conditions are important in the pathophysiology of preterm delivery.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings of a higher plasma IL-6 level in early pregnancy in women with vitamin D insufficiency is in accordance with previous reports demonstrating higher levels of plasma IL-6 in patients with diabetes and vitamin D insufficiency (32). In healthy women with preterm delivery (33) a higher level of IL-6 has been documented, indicating that proinflammatory conditions are important in the pathophysiology of preterm delivery.…”
Section: Discussionsupporting
confidence: 92%
“…Few observational studies have reported that the prevalence and severity of vitamin D deficiency were high in patients with DFU (Tiwari, Pratyush, Gupta, & Singh, 2014;Tiwari et al, 2013). Hyperglycemia in diabetic patients disrupts the normal process of cytokine production (Naguib, Al-Mashat, Desta, & Graves, 2004), which in turn leads to the development of chronic wound (Agren et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous studies have revealed that patients with DFU had higher prevalence of VDD and lower vitamin D levels in comparison to diabetic patients without DFU [17,22,70,[80][81][82]. We reported that the prevalence of VDD in participants with DFU was about 80%.…”
Section: Discussionmentioning
confidence: 61%